Muscle Sentry® has no effect on total work performed and estimated MVO2 after high intensity short duration resistance training - Xu, J.; Farney, T. M.; Nelson, A. G. (International Journal of Exercise Science, 2020)
Supplements are widely used in recreational and professional participants; however, their claimed benefits are hardly to test. This study compared the total lifted numbers and post-exercise estimated MVO2 while subjects were treated with either Muscle Sentry® (MS) or placebo (PL), in a 7-day washout period. Participants (11 women, 10 men, 20-24 years) performed 3 sets to failure chest and leg press exercises at 8 RM with 2 min rest between sets. Each exercise was performed four times (2 × MS, 2 × PL) at the same time of the day separated by 48 h. The supplementation was ingested 40 min prior to perform the exercise. Prior to the exercise and immediately after each set, both HR and BP were obtained. The rate pressure product (RPP) was then calculated to determine estimated MVO2. Daily RPP and total weight lifted (chest + leg) for each supplementation were averaged. Normalized RPP was the ratio of averaged RPP and averaged total weight lifted. No treatment effect on chest, leg and total lift numbers, normalized post RPP (NPRPP), normalized RPPdiff (NRPPdiff) (p=0.94, 0.86, 0.87, 0.87, 0.43 respectively); No treatment effect on total lift numbers, NPRPP, NRPPdiff for gender (p=0.87, 0.95, 0.96 respectively). Ingestion of Muscle Sentry® 40 min prior to do 3 sets to failure of both chest and leg presses had no effect upon either total lift numbers or estimated MVO2. This suggests that, in some instances, the benefits of Muscle Sentry® are less than those claimed by the manufacturer.